Optimization of methods to assess mitochondrial DNA in archival paraffin-embedded tissues from mammary canine tumors Otimização dos métodos para avaliar o DNA mitocondrial obtido a partir de tumores mamários caninos incluídos em parafina - Angélica C. Bertagnolli; Valdemar Máximo; Bárbara van Asch; António Amorim; Luis Cirnes; Paula Soares; Geovanni D. Cassali (Sociedade Brasileira de Patologia Clínica, 2008)
In this study we describe the alterations used to extract and amplify mitochondrial desoxyribonucleic acid (DNA) from formalin-fixed paraffin-embedded samples of canine mammary tumors. The epithelial and mesenchymal components (chondromyxoid and chondroid) of each tumor, as well as the normal mammary gland tissues, were manually microdissected from 19 mixed canine mammary tumors (10 benign mixed tumors and nine carcinomas arising in mixed tumors). DNA was extracted by Invisorb® Spin Tissue Mini Kit, with protocol changes proposed by the manufacturer. A 273-bp fragment was amplified by polymerase chain reaction (PCR) and submitted to automatic sequence analysis. The fragment was successfully analyzed in 100% of the samples. However, an additional lysis step, the reduction of volume in buffer solutions and PCR, a higher annealing temperature and an increase in the number of PCR cycles were required. The initial PCR products were diluted and re-amplified in six samples so that they could be successfully analyzed. A presente comunicação descreve as modificações usadas para extrair e amplificar o DNA mitocondrial obtido de amostras de tumores mamários caninos fixados em formol tamponado a 10% e incluídos em parafina. Os componentes epiteliais e mesenquimais (condromixóide e condróide), bem como a mama normal adjacente, foram microdissectados manualmente de 19 tumores mamários (10 tumores mistos benignos e nove carcinomas em tumores mistos). O DNA foi extraído utilizando-se o Invisorb® Spin Tissue Mini Kit com modificações do protocolo proposto pelo fabricante. Um fragmento de 273-pb foi amplificado por reação em cadeia da polimerase (PCR) e seqüenciado em seqüenciador automático. O fragmento foi analisado em 100% das amostras, entretanto modificações como lise adicional, redução do volume das soluções de extração e PCR, aumento da temperatura de anelamento e do número de ciclos de amplificação foram necessárias. Em seis amostras os produtos iniciais de PCR foram diluídos e reamplificados para obtenção de sucesso.